Influence of Culture and Religion on Anxiety Patients: A Qualitative Study in Sabah - Atiqah Chew Abdullah; Salami Mutiu Olagoke; Asrenee Ab Razak; Asma Perveen; Tze, Nicholas; Walton Wider; Diana Nabila Chau Abdullah (Journal for Re Attach Therapy and Developmental Diversities, 2023)
Introduction: Anxiety is a common mental health disorder that significantly impacts the individual and socioeconomic. Sabah has the highest prevalence of mental health disorders among Malaysian states. The people of Sabah are varying in ethnicities with vast cultural beliefs embedded in the society, therefore understanding cultural and religious factors is essential for the implementation of effective approaches to mental health care. Objectives: To explore the influence of cultural and religious practice on the respondents’ anxiety levels. Methods: A total of 15 multiethnic participants residing in Sabah were recruited and interviewed for this study, in which participants were either patients with panic disorder or generalize anxiety disorder. Interpretative phenomenological perspective was employed through learning about the subjective experience and meaning making of the participants interviewed. Primary data obtained from the qualitative study were then thematically analysed using Nvivo software Results: Results showed that religious practices helped anxiety patients cope with their disorder, increase resilience, and give them strength and motivation; while cultural practices did not. Conclusions: Anxiety is chosen as a focus because of its high prevalence, especially during the COVID-19 pandemic. This study emphasized the importance of understanding the role of culture and religion in helping the respondents cope with their disorders. The findings of this study could help define more effective ways in raising awareness and encouraging health-promoting behaviour such as treatment-seeking among the community in Sabah.